2008
DOI: 10.1088/0957-4484/19/45/455606
|View full text |Cite
|
Sign up to set email alerts
|

The influence of substrate temperature on InAsN quantum dots grown by molecular beam epitaxy

Abstract: The effect of substrate temperature, 390-480 °C, during molecular beam epitaxy growth of InAsN quantum dots has been studied. The quantum dot formation was studied in situ, and it is shown that the quantum dots are close to fully relaxed within 4 monolayers (ML) of InAsN deposition. Further, the indium concentration was estimated to be 84%, 67%, 55% and 31% for 4 ML thick quantum dots grown at 390, 420, 450 and 480 °C, respectively. Thus, Ga incorporation was demonstrated at all substrate temperatures. The dot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
3
0
1
Order By: Relevance
“…Такие изменения параметров масси-ва самоорганизованных островков/кластеров связаны с уменьшением длины поверхностной диффузии адатомов в режиме МЛЭ [24][25][26][27][28][29][30][31][32]. Действительно, в режиме АСЭ поочередное осаждение In и Sb приводит к появлению периодов времени, когда материала III группы на росто-вой поверхности больше, чем V группы, что осложняет встраивание атомов металла в кристалл и, следователь-но, увеличивает L d в сравнении с ростом в режиме МЛЭ.…”
Section: обсуждение результатовunclassified
“…Такие изменения параметров масси-ва самоорганизованных островков/кластеров связаны с уменьшением длины поверхностной диффузии адатомов в режиме МЛЭ [24][25][26][27][28][29][30][31][32]. Действительно, в режиме АСЭ поочередное осаждение In и Sb приводит к появлению периодов времени, когда материала III группы на росто-вой поверхности больше, чем V группы, что осложняет встраивание атомов металла в кристалл и, следователь-но, увеличивает L d в сравнении с ростом в режиме МЛЭ.…”
Section: обсуждение результатовunclassified
“…Thereby, unintentional nitrogen incorporation due to background pressure can be avoided. Recent publications show the advantages of this chamber configuration compared to installing the plasma source at a standard cell flange [22,23]. Compared to systems where the nitrogen plasma source is installed at a normal cell flange and the flux is blocked by a mechanical shutter, the system with a vacuum valve offers the possibility to add nitrogen only to specific layers without releasing nitrogen to the rest of the structure.…”
Section: Experimental Setupsmentioning
confidence: 99%
“…This would benefit from cavity enhanced emission of such single QDs in Al(Ga)As/GaAs cavities at telecommunication wavelengths [21]. Therefore, recently, GaInAs(N) QDs with GaInAs(N) capping layers have attracted increasing research interest but as yet only ensemble measurements have been reported [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…for MBE growth or pulsed laser deposition. Methods like reflection high‐energy electron diffraction (RHEED) 2 or X‐ray diffraction 3, 4 established to standard tools. But there are only a few reports about the in situ investigation of the liquid–solid interface by X‐ray diffraction 5 and no one for LPE.…”
Section: Introductionmentioning
confidence: 99%